THE ROLE OF MANAGEMENT OF COMMUNITY READING GARDEN ( TBM) TO INCREASING THE MOTIVATION OF ADULTS TO READ WITH AN ANDRAGOGICAL APPROACH - Fauzi, Erwin Rifal; Nurhayati, Sri (IKIP Siliwangi Bandung, 2025)
The community reading garden is one of the extracurricular educational offerings. The right approach is needed in program implementation. TBM Silayung aims and focuses more on adult education/reawakening adult interest in reading. The right approach in this program is the andragogic approach. The andragogic approach is an approach that uses the principles of adult education. This principle is used because the majority of students are adults with different learning styles. Therefore, the application of the andragogic approach is necessary to motivate students to learn. The purpose of this study was to find out the role of Community Reading Gardens (TBM) managers in increasing adult reading motivation using the andragogic approach. Using a qualitative approach with descriptive methods and data collection techniques including observations, interviews and literature reviews. The TBM program aims to re-increase the demand for adult reading.